Convention Strategy of the Islamic Cultural in Responding to the Wahhabi Movement in Suralaga Village, East Lombok Regency - Azizah, Lutfatul; Jannah, Zuhrupatul; Rahim, Abdul; Halimi, Ahmad (Potret Pemikiran, 2023)
The presence of Wahhabi ideology within the cultural Islamic society has led to a stark dichotomy, primarily due to the Wahhabi community's puritanical stance that opposes certain religious traditions observed by the broader Islamic community. Specifically, the Wahhabi group rejects customary celebrations on holy days, citing a lack of explicit guidance in the Qur'an and al-Hadith regarding these practices. This study aims to delve into the perceptions of individuals outside the Wahhabi group within Suralaga Village, exploring their responses to Wahhabi lectures and activities. Additionally, it seeks to understand the role played by these individuals in maintaining socio-religious harmony, encompassing the involvement of governmental and religious authorities in the village. The research objectives are multifaceted, aiming not only to comprehend external responses to Wahhabi teachings but also to identify behavioral patterns exhibited by the cultural Islamic community in response to the assertiveness of the Wahhabi movement. Furthermore, the study seeks to uncover the strategies employed by the cultural Islamic community to foster moderate attitudes internally and within the Wahhabi group. The findings of this research illuminate the diverse attitudes embraced by the cultural Islamic community, such as Separation, Acceptance, Abandonment, and the prioritization of social over strict religious affiliations in response to Wahhabi da'wah. Moreover, the approach taken by the cultural Islamic community involves fostering socio-cultural solidarity and socio-political relations with the Wahhabi congregation, showcasing efforts to navigate differences and promote social cohesion while embracing moderation within the community.